Peran A.M. Thalib dalam Mempertahankan Kemerdekaan Indonesia Tahun 1948 - Meilinda, Aisyah; Isbandiyah; Irwansyah (Kaganga:Jurnal Pendidikan Sejarah dan Riset Sosial Humaniora, 2025)
This study aims to determine and analyze the role of A.M. Thalib in maintaining Indonesian independence in South Sumatra in 1948. This study uses a historical method that includes four stages, namely heuristics (collecting sources), source criticism (analysis of the authenticity and credibility of sources), interpretation (interpretation of historical data), and historiography (writing history). The results of the study indicate that A.M. Thalib had an important role in maintaining Indonesian independence, especially through his role as a broadcaster and fighter who used the Radio Republik Indonesia (RRI) media to ignite the spirit of the people's struggle. He was also involved in efforts to defend Palembang from Dutch attacks and actively organized youth and the community. The conclusion of this study confirms that A.M. Thalib was one of the local figures who was influential in maintaining Indonesian sovereignty in the South Sumatra region. His role made a significant contribution in building the spirit of nationalism and solidarity of the people in the early days of independence. Keywords: A.M. Thalib, Indonesian Independence, Historical Method, Radio Republik Indonesia (RRI).